2016
DOI: 10.1111/jcmm.12827
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold nitric oxide synthase inhibition improves synergistic effects of subthreshold MMP‐2/MLCK‐mediated cardiomyocyte protection from hypoxic injury

Abstract: Injury of myocardium during ischaemia/reperfusion (I/R) is a complex and multifactorial process involving uncontrolled protein phosphorylation, nitration/nitrosylation by increased production of nitric oxide and accelerated contractile protein degradation by matrix metalloproteinase‐2 (MMP‐2). It has been shown that simultaneous inhibition of MMP‐2 with doxycycline (Doxy) and myosin light chain kinase (MLCK) with ML‐7 at subthreshold concentrations protects the heart from contractile dysfunction triggered by I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…In conclusion, this study confirmed our previous results [3,16] that showed that coadministration of subthreshold doses of Doxy, L-NAME, and ML-7 serves cardioprotective. Additionally, this study provided an important insight into understanding the interaction of iNOS, eNOS, and ADMA, which is crucial for the development of the therapy beneficial for patients after myocardial infarction.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In conclusion, this study confirmed our previous results [3,16] that showed that coadministration of subthreshold doses of Doxy, L-NAME, and ML-7 serves cardioprotective. Additionally, this study provided an important insight into understanding the interaction of iNOS, eNOS, and ADMA, which is crucial for the development of the therapy beneficial for patients after myocardial infarction.…”
Section: Resultssupporting
confidence: 92%
“…However, subsequently, it leads to ischemia/reperfusion injury (IRI), resulting in a cascade of processes detrimental to cardiac tissue. Impaired nitric oxide (NO) metabolism along with oxidative stress is known to be an important factor contributing to the pathophysiology of cardiovascular disorders, including myocardial infarction [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that co-administration of low concentrations of drugs that prevent both phosphorylation and degradation of MLC1 improves cardiac mechanical function after I/R (27). Additionally, in a model of hypoxia-reoxygenation with use of isolated cardiomiocytes we showed that the combination of a subthreshold concentration of a NOS inhibitor with subthreshold concentrations of MLCK and MMP-2 inhibitors resulted in full recovery of cardiomyocyte contractility (28). Thus, we propose that an alternative to monotherapy at full therapeutic dose (often limited by cytotoxicity) is the use of combination therapy at lower therapeutic concentrations without loss of protective effects with the added advantage of limiting adverse physiological side effects.…”
Section: L-name Improves Doxycycline and Ml-7 Cardioprotection From Omentioning
confidence: 87%
“…It is well accepted, that one of the main factors contributing to the pathogenesis of I/R injury is an increased activity of matrix metalloproteinases (MMPs) (1,2) and degradation of contractile proteins (3-6). Recently we showed that the co-administration of a combination of low, subthreshold concentrations of MMP-2 and MLCK inhibitors is as effective and protective against I/R as the same inhibitors given alone at full protective doses (27,28). In addition, protective doses of single drug often exhibit undesired effects.…”
Section: Discussionmentioning
confidence: 99%